Comparison of Mean Blood Loss in Women Undergoing Cesarean Section Who Received Tranexamic Acid Preoperative Versus Those Didn’t Receive It - Afridi, Sumaira; Shabbir, Saima; Aziz, Sumaiya; Arif, Mehnaz; Younus, Maryam (Indus Journal of Bioscience Research, 2025)
Background: Postpartum hemorrhage (PPH) after cesarean sections is one of the major risk factors to maternal mortality and morbidity Even though tranexamic acid (TXA) is now recommended for the PPH treatment, it is still not suggested to use it as a prophylactic intervention during delivery. The study aim is to evaluate the comparison of the effect of Tranexamic acid (TXA) versus control group in pregnant women undergoing Cesarean section. Methods: This Randomized controlled trial study was conducted at Labour room and operation theatre of KVSS Hospital during March-Oct 2022. One hundred pregnant women who had a cesarean-section participated in the study, Two-groups of women were formed: the study group had a slow IV-infusion of 2grams of tranexamic acid (20 ml volume) mixed in 50ml of normal saline solution 0.9% (70ml volume) under spinal anesthesia, while the control group receive normal saline. Blood volume, estimated blood loss, and preoperative and postoperative hemocrit were documented. Results: As compared to control group, mean blood loss in TXA group found significantly less during cesarean delivery and blood loss 2-hours from end of CS (p≤0.05). This was reflected in the change of Hb and hematocrit values, which also showed highly significant statistical difference (p≤0.001). Conclusion: Without causing any immediate risk to the woman or the newborn, tranexamic acid treatment during an elective cesarean section has been shown to be beneficial in minimizing blood loss, which sequentially reduces the risk of PPH.